2006
DOI: 10.4315/0362-028x-69.11.2697
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Environmental Evaluations To Identify Food Safety Differences between Outbreak and Nonoutbreak Restaurants

Abstract: Restaurants are important settings for foodborne disease transmission. The Environmental Health Specialists Network (EHS-Net) was established to identify underlying factors contributing to disease outbreaks and to translate those findings into improved prevention efforts. From June 2002 through June 2003, EHS-Net conducted systematic environmental evaluations in 22 restaurants in which outbreaks had occurred and 347 restaurants in which outbreaks had not occurred. Norovirus was the most common foodborne diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 10 publications
7
98
0
4
Order By: Relevance
“…In 2006, Hedberg et al (12) found that the presence of a CKM had a protective effect with respect to foodborne illness outbreaks. Thus, the presence of a CKM may help to improve food safety practices among food workers and ultimately reduce foodborne illness.…”
mentioning
confidence: 99%
“…In 2006, Hedberg et al (12) found that the presence of a CKM had a protective effect with respect to foodborne illness outbreaks. Thus, the presence of a CKM may help to improve food safety practices among food workers and ultimately reduce foodborne illness.…”
mentioning
confidence: 99%
“…Proper hand sanitation has proven to be critical during distribution and consumption of food (Armed Forces Health Surveillance Center, 2014; Arness et al, 2000;Hedberg et al, 2006). No studies have been conducted within a U.S. Army dining facility.…”
Section: Justificationmentioning
confidence: 99%
“…Proper hand sanitation is critical during preparation, distribution, and consumption of food, whether in the home or a congregate environment, such as a dining facility (Fein, Lin, & Levy, 1995;Greig, Todd, Bartleson, & Michaels, 2007;Hedberg et al, 2006). Proper hand washing with soap and water, then drying, is a proven and effective method of hand sanitation (Curtis & Cairncross, 2003;Todd, Michaels, Greig, Smith, & Bartleson, 2009).…”
Section: Chapter 2 -Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, respondents' perceptions about the researched subjects were heterogeneous regardless if they participated in good manufacturing practices training or if they worked in establishments where consulting service or a technical manager was available. (HEDBERG et al, 2006;GERMANO;GERMANO, 2008).…”
mentioning
confidence: 99%